Acute coronary artery occlusion and ischemia‐related ventricular tachycardia during catheter ablation in the right ventricular outflow tract. (18th November 2020) - Nakatani, Yosuke; Vlachos, Konstantinos; Ramirez, F. Daniel; Nakashima, Takashi; Jais, Pierre; Sacher, Frédéric; Romain, Tixier
Abstract: Coronary artery injury is a rare complication of catheter ablation in the right ventricular outflow tract (RVOT). Furthermore, acute myocardial ischemia usually causes polymorphic ventricular tachycardia (VT) or ventricular fibrillation. We herein describe a case in which catheter ablation for VT originating from the RVOT provoked ischemia‐related VTs due to acute occlusion of the left anterior descending artery.